Implikasi Disfungsi Manajemen KPU Kota Palembang terhadap Kinerja Badan Ad Hoc pada Pilkada 2018 - Trisnawati, Emi; Hertanto, Hertanto; Mukhlis, Maulana (Jurnal Analisis Sosial Politik, 2019)
Management functions of General Election Commission of Palembang hold an important role in terms of ad hoc electoral body governance. This research is to describe those functions, to explain the performance of ad hoc electoral body, and to analyze the management dysfunctional implications towards the performance of the ad hoc electoral body in Palembang Mayor Election on 2018. By using descriptive-qualitative research method, data and information of this research was collected through interviews and documentation sources. The research results shows that : (1) In terms of ad hoc electoral body governance, there has been a dysfunctional in planning management indicated by the recruitment process which was affected by political interest and personal relation, the lack of supervision and coordination amongst the elements of General Election Commission of Palembang and also with the ad hoc electoral body, (2) the performance of ad hoc electoral body based on personal factor shows low quality of work because of the age factor and also low electoral ability and knowledge, leadership factor was not performed properly, inadequate team factor, system factor also affect the work performance of ad hoc electoral body due to the facility support from the local government that affects their neutrality as contextual/situasional factor, (3) the dysfunctional management of General Election Commission of Palembang in Palembang Mayor Election on 2018 had impacted on the performance of ad hoc electoral body. Manajemen KPU Kota Palembang dalam tata kelola Badan ad hoc berperan penting. Penelitian ini bertujuan mengetahui fungsi manajemen yang dilakukan oleh KPU Kota Palembang dalam tata kelola Badan ad hoc, mengetahui kinerja Badan ad hoc, serta mengetahui implikasi disfungsi manajemen KPU Kota Palembang terhadap kinerja Badan ad hoc pada Pilkada 2018. Metode penelitian ini deksriptif kualitatif, data informasi penelitian diperoleh dari wawancara, dan dokumentasi. Hasil penelitian menunjukkan: (1) Manajemen KPU Kota Palembang dalam tata kelola Badan ad hoc pada Pilkada 2018 terjadi disfungsi, dilihat dari fungsi perencanaan pada proses rekrutmen Badan ad hoc masih mengutamakan kepentingan politik dan unsur kedekatan personal, fungsi pengawasan tidak berjalan, serta kurangnya koordinasi antara Sekretariat dengan Komisioner KPU Kota Palembang, dan KPU dengan Badan ad hoc (2) kinerja Badan ad hoc dilihat dari personal factor tidak menghasilkan kualitas kerja yang baik dikarenakan faktor usia, minimnya pengetahuan di bidang kepemiluan, leadership factor tidak berjalan sesuai dengan tupoksinya, team factor kurang maksimal, system factor mempengaruhi kinerja Badan ad hoc dikarenakan sarana dan prasarana masih difasilitasi oleh Pemerintah Daerah, sehingga contextual/situasional factor memicu ketidaknetralan Badan ad hoc dalam melaksanakan tugas dan wewenangnya sebagai penyelenggara pemilu, (3) disfungsi manajemen KPU Kota Palembang berimplikasi pada rendahnya kinerja Badan ad hoc.